2017
DOI: 10.7150/ijbs.17240
|View full text |Cite
|
Sign up to set email alerts
|

Reverse the Resistance to PARP Inhibitors

Abstract: One of the DNA repair machineries is activated by Poly (ADP-ribose) Polymerase (PARP) enzyme. Particularly, this enzyme is involved in repair of damages to single-strand DNA, thus decreasing the chances of generating double-strand breaks in the genome. Therefore, the concept to block PARP enzymes by PARP inhibitor (PARPi) was appreciated in cancer treatment. PARPi has been designed and tested for many years and became a potential supplement for the conventional chemotherapy. However, increasing evidence indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 119 publications
(184 reference statements)
0
43
0
Order By: Relevance
“…For this reason we were able to identify two additional tumor cases with mutations in other DNA damage response genes than BRCA1/2 (PALB2 and NBN), which might also respond to PARP-inhibitor therapy. BRCA1/ 2-mutated ovarian cancers respond to platinum-based chemotherapy and PARP-inhibition therapy and current studies further investigate the effect of PARP-inhibition both on other cancer entities and on cancers driven by pathogenic mutations in other DDR-genes [37][38][39]. With regards to this, detection of SNVs and CNVs in a larger number of genes becomes increasingly important.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason we were able to identify two additional tumor cases with mutations in other DNA damage response genes than BRCA1/2 (PALB2 and NBN), which might also respond to PARP-inhibitor therapy. BRCA1/ 2-mutated ovarian cancers respond to platinum-based chemotherapy and PARP-inhibition therapy and current studies further investigate the effect of PARP-inhibition both on other cancer entities and on cancers driven by pathogenic mutations in other DDR-genes [37][38][39]. With regards to this, detection of SNVs and CNVs in a larger number of genes becomes increasingly important.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic reexpression of BRCA1, BRCA1 deletion isoforms, genetic reversion of BRCA, or replication machinery stabilization may partially restore the HR molecular pathway and mediate PARPi resistance. Additionally, researchers showed that several miRNAs could induce PARPi resistance via balancing NHEJ and DSB repair pathways or by suppressing HR repair proteins (43). Here, we demonstrated that let-7e decreased the expression of BRCA1 and Rad51 and suppressed DSB repairs through targeting PARP1.…”
Section: Discussionmentioning
confidence: 61%
“…It is well established that the "BRCAness" phenotype of the breast cancer cells plays a crucial role toward PARPi sensitivity and conferring the concept of synthetic lethality, and our results are consistent with that concept. Partial restoration of the homologous recombination DNA repair pathway can lead to resistance to PARPi (27), and upregulation of RAD51 in BRCA1defective cells is associated with resistance to PARPi (20). It is worth noting that our results of olaparib resistance in different BRCA1 mutant cells due to EMI1 downregulation that were associated with high RAD51 levels are in line with previous results done either in BRCA1 mutant cancer cells (20) or BRCA2 mutant ones (25).…”
Section: Discussionmentioning
confidence: 99%